Genomics combined with a protein informatics platform to assess a novel pathogenic variant c.1024 A>G (p.K342E) in OPA1 in a patient with autosomal dominant optic atrophy. (1st November 2020) - Ahuja, Abhimanyu S.; Selvam, Pavalan; Vadlamudi, Charitha; Chopra, Hayley; Richter, John E.; Macklin, Sarah K.; Samreen, Ayesha; Helmi, Haytham; Mohammaad, Ahmed N.; Hines, Stephanie; Davila, Maria C.; Atwal, Paldeep S.; et al.
ABSTRACT: Background: Autosomal Dominant Optic Atrophy (ADOA) is caused by mutations in the Optic Atrophy 1 Gene which disrupts the OPA1 protein. This disruption affects the normal function of the protein; impairs fusion of the mitochondrial inner membrane; and prevents normal OPA1 protein degradation. These events cause damage in retinal ganglion cells that could affect the patients with symptoms ranging from none to legally blind. Materials and methods: Our study identifies a missense variant mutation, c.1024 A > G (p.K342E), in OPA1 gene causing ADOA. Diagnosed clinically in three family members and the presence of this mutation was confirmed in two members by genetic testing. Pathogenic variants in OPA1 impact the secondary protein structure and function by causing non-conservative amino acid substitutions. We also modeled this mutation and compared it to the wild type using statistical mechanics. Results and conclusions: The proband's pathogenic variant, c.1024 A > G (p.K342E), is located in the GTPase domain of OPA1 and causes changes in the protein structure by affecting the oligomerization pattern thus resulting in ADOA. Identifying the pathogenic potential of the missense mutations in the OPA1 gene using neoteric protein modeling techniques would help in the early detection of ADOA in patients who have family history of blindness. This action would help in providing early follow up, possible treatment in the future, and genetic counseling. Abbreviations: ADOA: Autosomal Dominant Optic Atrophy; CYCS: Caspase Activator Cytochrome C; OPA1: Optic Atrophy Gene 1; RGC: Retinal Ganglion Cells; VUS: Variant of Uncertain Significance